Identifying and understanding how critical landscapes for carbon sequestration respond to development for low carbon energy production: Insight to inform optimal land planning and management strategies - Waldron, Susan; Heal, Kate; Elayouty, Amira; Flowers, Hugh; Scott, E. Marian; Zheng, Ying; Murray, Helen; Coleman, Martin; Phin, Antony; Pickard, Amy (Journal of environmental management, 2025)
Wind farms can mitigate increasing CO2 emissions by fossil-fuel free energy generation. However, landscape disturbance during development must not have lasting impacts on C sequestration, an ecosystem service. To understand how a critical carbon landscape responds to wind farm development, we monitored for 10 years dissolved organic carbon (DOC) export in five catchments draining Europe's second largest onshore wind farm, Whitelee, UK. The DOC flux trend and seasonality were modelled using Generalised Additive and Mixed Models, novelly using first derivatives of trends to identify responses to wind farm development. Unlike a nearby, minimally-disturbed catchment, Whitelee catchment DOC fluxes increased over the decade, tracking successive phases of wind farm development, particularly forest felling to enable turbine location. Inter-catchment differences in the rate of DOC flux, where slowing suggests recovery (not always evident), reflect differing intensity (timing and spatial reach) of catchment disturbance. However, increased DOC flux approximated 3.5 % maximum of C likely sequestered and therefore soil C sequestration is unlikely to be compromised unless the soils are highly degraded and close to not being a C sink. For the greenest energy transition, responsible planning should minimise C losses, even when small, and in a critical landscape may require consideration of impact on other ecosystem services. For example, deterioration in quality of potable water supply occurred within the observation period. Ongoing provisioning of multiple ecosystem services from critical carbon landscapes requires planning. We demonstrate an example of such an approach for wind farm development considering in priority order carbon storage, forest products, potable water supply. Our findings are relevant to integrated landscape planning and management in temperate and high latitude/altitude peatlands globally that are subject to wind energy development and/or forest felling. [Display omitted] •Decadal dissolved organic C (DOC) flux from 5 disturbed peaty catchments quantified.•Wind farm catchments after 10 years exporting more DOC than prior to development.•First derivatives analysis shows DOC flux trends change with wind farm development.•Increased DOC flux is unlikely to compromise net C sequestration in healthy soils.•Increased DOC flux may affect other ecosystem services – planning framework presented.